SPA-SARL-SNC أثر الشكل القانوني على محاسبة وجباية الشركات التجارية دراسة مقارنة - العوامر العايش; غندير مبروك صالح; كنيوة محمد البشير (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة إلى تحليل تأثير األشكال القانونية للشركات التجارية )SPA، SARL، SNC )على نظامها المحاسبي والجبائي، مع التركيز على اختالف المعالجة المحاسبية )كقيود التأسيس، تعديل رأس المال، توزيع األرباح( وااللتزامات الضريبية )كضريبة أرباح الشركات، والضريبة على الدخل اإلجمالي(. كما تسعى إلى تعزيز الفهم العلمي للممارسات المحاسبية والضريبية، وتحسين القرارات االستراتيجية ِّل التنظيم المحاسبي. قلل التكاليف الضريبية وي الختيار الشكل القانوني األمثل الذي ي برز االختالفات الجوهرية في األنظمة المحاسبية والجبائية بين اعتمدت الد ارسة على منهجية تحليلية ت األشكال القانونية. وتوصلت النتائج إلى أن الشكل القانوني للشركة يؤثر بشكل مباشر على طريقة معالجة ا للمعاييُساهم اختيار الشكل القانوني المناسب )وفق العمليات المحاسبية وحجم التكاليف الجبائية، حيث ي المحاسبية أو الضريبية( في تسهيل التنظيم المحاسبي أو تقليل األعباء الضريبي "This study analyzes the impact of legal forms of commercial enterprises (Public Limited Company/SPA, Limited Liability Company/SARL, General Partnership/SNC) on their accounting and tax systems, focusing on differences in accounting treatment (capital registration, capital modification, profit distribution) and tax obligations (corporate profit tax, global income tax). It aims to enhance the scientific understanding of accounting and tax practices, and to optimize strategic decisions for selecting the most suitable legal form to reduce tax costs and facilitate accounting organization.. The study relies on an analytical methodology highlighting fundamental differences between accounting and tax regimes according to legal forms. Results show that the legal form directly influences the treatment of accounting operations and the level of tax costs. Choosing an appropriate legal form (according to accounting or tax standards) facilitates accounting organization or reduces tax burdens..
ماستر العلوم المالية والمحاسبية
Keywords: الاشكال القانونية; محاسبة وجباية; الشركات التجارية; محاسبة الشركات; Legal forms; accounting and taxation; commercial enterprises; corporate accounting.